Designing Place-Based Interventions for Sustainability and Replicability: The Case of GO! Austin/VAMOS! Austin - Hussaini, Aliya; Pulido, Carmen Llanes; Basu, Semonti; Ranjit, Nalini (Frontiers in Public Health, 2018)
Place-based health efforts account for the role of the community environment in shaping decisions and circumstances that affect population well-being. Such efforts, rooted as they are in the theory that health is socially determined, mobilize resources for health promotion that are not typically used, and offer a more informed and robust way of promoting health outcomes within a community. Common criticisms of place-based work include the difficulty of replication, since engagement is so specific to a place, and limited sustainability of the work, in the absence of continued institutional structures, both within the community and supporting structures outside the community, to keep these initiatives resilient. This paper describes a place-based initiative, GO! Austin/VAMOS! Austin (GAVA), which was designed to harness the strengths of place based work – namely its specificity to place and community. From the start, the project was designed to balance this specificity with a focus on developing and utilizing a standardized set of evidence-informed implementation and evaluation approaches and tools that were flexible enough to be modified for specific settings. This was accompanied by an emphasis on leadership and capacity building within resident leaders, which provided for informed intervention and demand building capacity, but also for longevity as partners, philanthropic and otherwise, moved in and out of the work.